(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Life Insurance Industry in India has been facing many problems and challenges for the last decade. But still, it has attained a very good position among other financial services. The industry has witnessed remarkable growth with the change in the awareness level of consumers and their perception about life insurance. The life insurance sector of India was opened in 1999 for the private sector and since then this sector has seen an immense change because the Private life insurance companies have brought in professionalism, innovations, technology, new products, and operational efficiency in the life insurance sector of India. Earlier Life Insurance Corporation (LIC) has a monopoly in this sector but now it is facing tough competition from the private players. The focus of this paper is to compare the performance of LIC and private life insurance companies in India for the last few years. It also examines the effect of private life insurance companies on the business of LIC and up to what extent LIC is able to retain its market share in this business.